Revolutionizing ELISA: a one-step blocking approach using lipid bilayer coatings - An, Kyongman (2024)
Enzyme-linked immunosorbent assay (ELISA) is an essential technique for biomolecule detection in diagnostics and research, but traditional protocols are time-consuming and variable. Conventional blocking agents like bovine serum albumin (BSA) pose ethical issues and potential assay interference. This study presents a one-step lipid-blocking approach to simplify the ELISA procedure. Compared to conventional blockers, the Lipid Universal Coating Assembly (LUCA) antifouling blocker showed comparable sensitivity while significantly reducing processing time and steps. Furthermore, it showed improved co-blocking efficacy and signal intensity in conventional protocols when combined with minimal BSA concentrations. Stability tests under accelerated aging confirmed the robustness of the LUCA antifouling blocker. Additionally, it effectively facilitated antibody detection for COVID-19 antigens in direct ELISA and human IL-6 antigen in Sandwich ELISA, suggesting its versatile applicability. Taken together, our findings reveal that one-step lipid blocking not only streamlines the ELISA process but also maintains high sensitivity and specificity, providing an efficient, user-friendly, and environmentally friendly alternative to traditional ELISA blockers and a robust platform for rapid diagnostics.